2013
DOI: 10.1371/journal.pone.0055875
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Reduces Wound-Induced Activation of Microbicidal Potential of Ex Vivo Isolated Human Monocyte-Derived Macrophages

Abstract: BackgroundPsychological stress delays wound healing but the precise underlying mechanisms are unclear. Macrophages play an important role in wound healing, in particular by killing microbes. We hypothesized that (a) acute psychological stress reduces wound-induced activation of microbicidal potential of human monocyte-derived macrophages (HMDM), and (b) that these reductions are modulated by stress hormone release.MethodsFourty-one healthy men (mean age 35±13 years) were randomly assigned to either a stress or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
(68 reference statements)
1
16
0
1
Order By: Relevance
“…Skin tissue harvested in the absence of injected epinephrine, and within 30 minutes of surgical injury, was processed for catecholamine analysis. Levels range from those reported in nonstressed muscle (20 pg mg À 1 , (Ohkuwa et al, 2005)) to levels that approximate those found in human serum (B700 ng ml À 1 , (Kuebler et al, 2013)). Thus, it is clear that the wound microenvironment is one wherein norepinephrine is present, and levels may vary widely.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Skin tissue harvested in the absence of injected epinephrine, and within 30 minutes of surgical injury, was processed for catecholamine analysis. Levels range from those reported in nonstressed muscle (20 pg mg À 1 , (Ohkuwa et al, 2005)) to levels that approximate those found in human serum (B700 ng ml À 1 , (Kuebler et al, 2013)). Thus, it is clear that the wound microenvironment is one wherein norepinephrine is present, and levels may vary widely.…”
Section: Discussionmentioning
confidence: 74%
“…However, the role of systemic elevation of norepinephrine is less clear. Although depletion of systemic norepinephrine impairs healing (Gosain et al, 2006), acute increases in norepinephrine could impair healing by decreasing macrophage efficiency in generating microbicidal oxidizing agents (Kuebler et al, 2013). The differences in the magnitude of the systemic elevation and the persistence of this elevation may explain the discrepancy, and future studies will be needed to determine the effects of stress levels of systemic norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling interval for every inflammatory measure 133 was chosen based on previous stress studies and in part further 134 clarified by kinetic testing. Our main hypotheses were that (1) 135 acute psychosocial stress induces rapid increases in NF-jB DNA 136 binding activity, as well as delayed increases in both mRNA and 137 plasma levels of the pro-inflammatory cytokines IL-1ß and IL- 6,138 and that (2) This study has been conducted within a project assessing the 145 stress reactivity of immune measures (Kuebler et al, 2013) Participants of the stress and control group reported to the lab-167 oratory by 10 a.m. and had to abstain from extensive physical exer-168 cise, alcohol, and caffeinated beverages during the previous 24 h. 169 Participants were given calorically standardized food with compa-170 rable amounts of macro-nutritional composition (i.e. fat, protein, 171 and carbohydrate) and an indwelling venous catheter was inserted.…”
mentioning
confidence: 99%
“…The objective of the current study was to investigate in a secondary analysis of our previous study (Kuebler, Wirtz et al., ) whether anticipatory cognitive stress appraisal modulates the observed wound‐induced activation of macrophage microbicidal potential in acutely stressed (stress wound group) compared to nonstressed men (nonstress wound group). To preactivate circulating monocytes as precursors of later M1 macrophages in vivo, we inserted a venous catheter long enough to supposedly initiate wound‐healing processes (Kuebler, Ehlert et al., ; Kuebler, Wirtz et al., ). For psychosocial stress induction, we used the Trier Social Stress Test (TSST), which evokes profound psychological and physiological stress responses in a highly standardized and reliable manner (Dickerson & Kemeny, ; Kirschbaum, Pirke, & Hellhammer, ).…”
mentioning
confidence: 98%
“…We recently found that wound‐induced activation of microbicidal potential (i.e., superoxide anion production) of human macrophages is suppressed by acute psychosocial stress (Kuebler, Wirtz, Sakai, Stemmer, & Ehlert, ). Macrophages are tissue‐resident immune cells that are derived from blood monocytes.…”
mentioning
confidence: 99%